D' Galary Shop / Nur Syafiqah Sheikh Munir … [et.al.] - Sheikh Munir, Nur Syafiqah; Wan Adnan, Wan Ezaty Arifa; Ibrahim, Alifah; Mohamed Asri, Siti Nurul Ain; Jaffry, Sheril Alisa (2012)
The name of our company is D'Galary Shop. The business is in form of partnership which consists of five members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is trading as well sell other people product at our bundle shop. We also have a waiting area for our customers to wait their couple. Our business operation is at 8.00 am to 5.00 pm every day. There are no sleeping partners and all are entitled to participate in the business management. We agreed that Nur Syafiqah Bt Sheikh Munir is our General Manager, Wan Ezaty Arifa Bt Wan Adnan, Marketing Manager, Siti Nurul Ain Bt Muhamed Asri, Administration Manager, Alifah Binti Ibrahim, Operation Manager and Sheril Alisa Bt Jaffry, Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skill and ability.